Manufacturers and Industrial Development Policy in Hamilton, 1890-1910 - Middleton, Diana; Walker, David (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1980)
After failing to establish Hamilton as a major wholesaling centre, businessmen in the city concentrated their attentions increasingly on the manufacturing sector. City Council policies were extremely supportive of this focus, particularly in the period from 1890 to 1910, which is examined in this paper. Manufacturers themselves, however, are shown to have played a minor role in Council's activities. None of the key figures in promoting pro-development policies in Hamilton were manufacturers, despite the fact that those policies were designed primarily to stimulate manufacturing. At the forefront, rather, were professional men with business interests, supported mainly by merchants.